Test Systems to Study the Structure and Function of Uncoupling Protein 1: A Critical Overview - Hirschberg, Verena; Fromme, Tobias; Klingenspor, Martin (Frontiers in Endocrinology, 2011)
The discovery of active brown adipose tissue (BAT) in healthy adult humans has renewed interest in the biology of this organ. BAT is capable of distributing nutrient energy in the form of heat allowing small mammals to efficiently defend their body temperature when acutely exposed to the cold. On the other hand BAT might be a target for the treatment of obesity and related diseases, as its pharmacological activation could allow release of excess energy stored in white adipose tissue depots. Energy dissipation in BAT depends on the activity of uncoupling protein 1 (UCP1), therefore a BAT-based obesity therapy requires a detailed understanding of structure and function of UCP1. Although UCP1 has been in the focus of research since its discovery, central questions concerning its mechanistic function and regulation are not yet resolved. They have been addressed in native mitochondria but also in several test systems, which are generally used to lower inter-experimental variability and to simplify analysis conditions. Different test systems have contributed to our current knowledge about UCP1 but of course all of them have certain limitations. We here provide an overview about research on UCP1 structure and function in test systems. So far, these have nearly exclusively been employed to study rodent and not human UCP1. Considering that the amino acid sequence of mouse and human UCP1 is only 79% identical, it will be essential to test whether the human version has a similarly high catalytic activity, allowing a relevant amount of energy dissipation in human BAT. Besides the issue of comparable mechanistic function a sufficiently high expression level of human UCP1 is a further prerequisite for anti-obesity therapeutic potential. Treatments which induce BAT hyperplasia and UCP1 expression in humans might therefore be equally important to discover as mere activators of the thermogenic process.